The collection - Museo Guggenheim Bilbao (2006)
[Dt.:] Das Guggenheim Bilbao ist ein Kunstmuseum für zeitgenössische und moderne Kunst in Spanien. Architekt des Gebäudes ist Frank O. Gehry. Die Website macht die Sammlung online recherchierbar. - [Engl.:] The Guggenheim Museum Bilbao is a modern and contemporary art museum designed by architect Frank O. Gehry and located in Bilbao, Basque Country, Spain. The website offers the collection online.